Exploring The Therapeutic Potential of Chalcone Derivatives: A Review of Biological Activities - Vani, V; Sreeja, Dr S; Devika, PS; Amina, T; Devapriya, S; Thrishala, Kennady (Asian Journal of Pharmaceutical Research and Development, 2025)
This article provides an overview of chalcones, focusing on their role in drug discovery. Chalcones are naturally occurring compounds with a β-unsaturated carbonyl aromatic ketone structure, commonly found in plants as precursors to flavonoids and isoflavones. The review emphasizes the potential of chalcone analogues in drug design, highlighting how structural modifications can enhance pharmacological activity and reduce toxicity. It categorizes the biological activities of chalcone derivatives, such as antidiabetic, antibacterial, anti-inflammatory, and neuroleptic effects. The article also explores the structure-activity relationship (SAR) and the mechanisms behind these effects, aiming to guide future research for developing safer and more effective drugs. Overall, chalcones are presented as versatile scaffolds for designing new therapeutic agents.